ASSESSING THE EFFECTIVENESS OF MANAGERS OF TECHNICAL COLLEGE WORKSHOPS: A CASE OF NORTH CENTRAL NIGERIA - Umar, Ibrahim Yakubu; Idris, Abubakar Mohammed; Audu, Rufai; Hamza, Abdulmajeed Bukar; Igwe, Christopher Obeta; Maaji, Shehu Abdullahi (Journal of Technical Education and Training, 2014)
This study assesses the effectiveness of managers of technical college workshops from the perspective of stakeholders in North Central Nigeria. A descriptive survey design was employed. Three research questions and two hypotheses were formulated to guide the study. A 35-item questionnaire developed by the researchers and validated by three experts was used to collect data from 101 administrators, 140 teachers, and 24 workshop personnel randomly sampled and stratified along trades in technical colleges. Mean was employed to answer the research questions while one way analysis of variance (ANOVA) was employed to test the hypotheses using Statistical Package for Social Sciences (SPSS) for data analysis. Result revealed that respondent shared similar opinions on the management of technical college workshops. It was therefore recommended that: The managers of the workshops should use alternative approaches in the management of workshop instead of waiting for government to provide everything; maintenance of tools should be a regular practice in the workshops; administrators should recommend teachers and workshop personnel to attend seminars regularly in order to update their knowledge on current practices in the management of technical college workshops among others.